Produção de briquetes a partir do lodo de esgoto sanitário e finos de carvão vegetal para geração de energia por combustão - Oliveira, Ricardo Sonsim de (2017)
Periodically several types of waste are produced and discarded in landfills. Among that waste there is the sewage sludge one of the biggest issues from environmental and financial perspective of sanitation companies. This study has as primary goal to evaluate the potencial production of sanitary sewage sludge briquettes and charcoal to be used as fuel, as well as to perform its physical and chemical characterization. The incorporation effect of the cooking residual oil by immersion method and in form of an additive incorporated directly into the briquette mixture composition was also evaluated. This fuel may be used in a combustion furnace boiler or biomass thermoelectric plants, which has same purpose as coal and wood. Fuel and mechanical characteristics of those briquettes as well as superior calorific value, ash content, volatile materials, fixed carbon, thermogravimetric analyzes and resistance to axial compression until the rupture were evaluated. There was experimental planning methodology known in the literature to verify the factors that interfere in the briquette production and its properties, as well as characterize briquette and raw materials. To investigate the best raw material proportions in the briquettes production and verify moisture effects and binder, a factorial experiment was performed under a randomized complete block design (DBC), maintaining a constant pressure (5 tons). This plan had as non-immersed briquettes blocks (1), and immersed ones (2) at 160 oC for a time of 100 seconds. After a negative effect on immersion process, due to low mechanical strength, a Plackett-Burman (PB) design was performed to evaluate moisture, binder, mixture, pressure effects as well as additive on mechanical briquettes resistance. This plan allowed to verify the variable effects in a reduced number of tests, PB (12) with a triple central point, totalizing a 15 tests matrix. Once the identification of most significant variables in the briquettes production, a larger number of trials and levels were planned, being central rotational compound (DCCR) design, applied on most significant variables of PB plan and additive, these plans showed best quantities and conditions required for briquettes production in terms of operations, transportation and storage as well as better energy efficiency. The best mixing condition that produced the briquette with the highest calorific value was 85% sewage sludge, 2.50% humidity, 7.50% additive and 8.75-ton pressure, besides a power 15.566 MJ.kg-1, capable of withstanding a pressure of 41.19 MPa (420 kgf cm-2) and a density of 1.311 g.cm-3, until rupture, thus the best briquette for transportation and handling. This work provides a suggested route to use sanitary sewage sludge in combination with charcoal fines to produce fuel in the form of briquettes. Besides these characteristics, morphological and compositional properties were studied by Scanning Electron Microscopy (SEM), Energy Dispersion Spectroscopy (EDS) and Fourier Transform Infrared Spectroscopy (FITIR) with attenuated total reflectance (ATR) as well as mechanical properties, visual analysis, granulometry tests and mechanical resistance. In this study with briquettes, power and mechanical resistance were investigated. With the test results, it was verified that sanitary sewage sludge has similar calorific value to other materials used for briquettes manufacture, being an excellent raw material for energy power by combustion in the form proposed by this study.